Clinical and Genetic Features of Warts, Hypogammaglobulinemia, Infections and Myelokathexis (WHIM) Syndrome - Dotta, L.; Tassone, L.; Badolato, R. (Current Molecular Medicine, 2011)
WHIM syndrome is a dominantly inherited primary immunodeficiency disorder representing the first identified example of human disease caused by mutations in the gene encoding for the chemokine receptor CXCR4. Pathogenesis is mediated by CXCR4 hyperfunction, leading to increased responsiveness to its unique ligand CXCL12 (also known as SDF-1). The altered CXCR4/CXCL12 interaction likely impairs cellular homeostasis and trafficking, resulting in immunological dysfunctions. The acronym WHIM resumes the main features of the syndrome: Warts, Hypogammaglobulinemia, Infections and Myelokathexis, which is abnormal retention of mature neutrophils in the bone marrow. WHIM patients suffer from recurrent bacterial infections since childhood and manifest a specific susceptibility to HPV infections. Hematological findings include neutropenia, lymphopenia and hypogammaglobulinemia. Because of the rarity of the disease and the heterogeneity in clinical presentation, diagnosis is often delayed. In the majority of patients, the phenotype is incomplete at the onset and WHIM syndrome is not suspected. Early identification may improve clinical and therapeutic management. Symptomatic treatments include G-CSF, substitutive immunoglobulins and antibiotic prophylaxis. A new therapeutic strategy might include the potent inhibitor of CXCR4 function plerixafor (Mozobil), as an agent specifically targeting the molecular defect in order to attenuate the phenotypic manifestations of the syndrome.
Keywords: CXCR4